Quantitative and Qualitative Literature Review of Augmented Reality in Teaching - Alptekin, Mesut; Froese, Lennart; Temmen, Katrin (Recent Trends of AI Technologies and Virtual Reality: Proceedings of 8th International Conference on Artificial Intelligence and Virtual Reality (AIVR 2024))
At Paderborn University, an AR-based app is being developed to prepare electrical engineering students for laboratory work. This paper aims to review the development of AR since 2010, particularly in technical university laboratories, through a systematic literature review. The study investigates AR's relevance in university teaching and examines specific AR applications in laboratory settings. Using a mixed-method approach, the research first employs a web crawler to gather 27,249 articles from the Lens database, followed by a bibliometric analysis. Further, Google Scholar is used to find 374 articles related to AR in scientific and technical laboratories, with 51 significant ones evaluated for application areas, findings, and other criteria. The findings show that AR in education is a growing trend, with a significant increase in publications and citations in recent years. Most studies focus on marker-based mobile AR applications, assessing aspects like motivation and user experience through surveys and interviews. However, there's limited research on AR's learning effectiveness in laboratories, partly due to the scarcity of technical equipment. One study found no significant learning impact from AR.
Keywords: Augmented Reality; Mixed Reality; Literature Review; Bibliometric Analysis; Education \and Laboratories

Revealing the Unspoken: Using LLMs to Mobilize and Enrich Tacit Knowledge in Event Logs of Knowledge-Intensive Processes - Brennig, Katharina (AMCIS 2025 Proceedings. 11.)
Large Language Models (LLMs) excel in understanding, generating, and processing human language, with growing adoption in process mining. Process mining relies on event logs that capture explicit process knowledge; however, knowledge-intensive processes (KIPs) in domains such as healthcare and product development depend on tacit knowledge, which is often absent from event logs. To bridge this gap, this study proposes a LLM-based framework for mobilizing tacit process knowledge and enriching event logs. A proof-of-concept is demonstrated using a KIP-specific LLM-driven conversational agent built on GPT-4o. The results indicate that LLMs can capture tacit process knowledge through targeted queries and systematically integrate it into event logs. This study presents a novel approach combining LLMs, knowledge management, and process mining, advancing the understanding and management of KIPs by enhancing knowledge accessibility and documentation.
Keywords: Process Mining; Large Language Model; Knowledge Management; Knowledge-Intensive Process; Tacit Knowledge

Vancomycin‐Modified DNA Origami Nanostructures for Targeting Bacterial Pathogens - Coşkuner Leineweber, Özge; Pothineni, Bhanu K.; Schumann, Nils; Hofmann, Ulrike; Möser, Christin; Smith, David M.; Grundmeier, Guido; Zhang, Yixin; Keller, Adrian (Small Structures)
The specific binding of DNA origami nanostructures (DONs) to bacteria is an important prerequisite for their application in pathogen targeting and antimicrobial drug delivery. So far, targeting bacteria with DONs has been achieved exclusively via aptamers, which suffer from drawbacks such as sensitivity toward environmental conditions and reduced binding after immobilization or conjugation. Here, an alternative approach is presented based on the modification of DONs with the cell wall‐binding glycopeptide antibiotic vancomycin. Using strain‐promoted azide‐alkyne cycloaddition, azide‐modified vancomycin is conjugated to selected staple strands and subsequently incorporated into 2D DON triangles. The resulting constructs show specific binding to the Gram‐positive species Bacillus subtilis ( B. subtilis ) and Staphylococcus capitis ( S. capitis ), and remarkably, to Gram‐negative Escherichia coli ( E. coli ), but no antimicrobial activity at vancomycin concentrations up to at least 2.91 μM. For B. subtilis and E. coli , DONs with vancomycin modifications on both sides exhibit better binding than DONs modified on only one side. However, both variants bind equally well to S. capitis . These results demonstrate the great potential of small molecule drug compounds for the robust, broad‐spectrum targeting of bacteria with DONs. Targeting a ubiquitous cell wall component of most pathogenic bacteria, vancomycin‐modified DONs have many potential applications in the prevention and treatment of nosocomial infections.

Security Implications of Malicious G-Codes in 3D Printing - Rossel, Jost; Mladenov, Vladislav; Wördenweber, Nico; Somorovsky, Juraj (Proceedings of the 34th USENIX Security Symposium)
The rapid growth of 3D printing technology has transformed a wide range of industries, enabling the on-demand production of complex objects, from aerospace components to medical devices. However, this technology also introduces significant security challenges. Previous research highlighted the security implications of G-Codes—commands used to control the printing process. These studies assumed powerful attackers and focused on manipulations of the printed models, leaving gaps in understanding the full attack potential. In this study, we systematically analyze security threats associated with 3D printing, focusing specifically on vulnerabilities caused by G-Code commands. We introduce attacks and attacker models that assume a less powerful adversary than traditionally considered, broadening the scope of potential security threats. Our findings show that even minimal access to the 3D printer can result in significant security breaches, such as unauthorized access to subsequent print jobs or persistent misconfiguration of the printer. We identify 278 potentially malicious G-Codes across the attack categories Information Disclosure, Denial of Service, and Model Manipulation. Our evaluation demonstrates the applicability of these attacks across various 3D printers and their firmware. Our findings underscore the need for a better standardization process of G-Codes and corresponding security best practices.

Improving wearable-based seizure prediction by feature fusion using an explainable growing network - Hasija, Tanuj; Kuschel, Maurice; Jackson, Michele; Dailey, Stephanie; Menne, Henric; Reinsberger, Claus; Vieluf, Solveig; Loddenkemper, Tobias (Artificial Intelligence in Medicine)

Centrifugal Differential Mobility Analysis—Validation and First Two-Dimensional Measurements - Rüther, Torben Norbert; Gröne, Sebastian; Dechert, Christopher; Schmid, Hans-Joachim (Powders)
To obtain a more comprehensive understanding of the specific properties of complex-shaped technical aerosols—such as partially sintered aggregates formed in combustion processes or structured particles resulting from complex synthesis processes—it is essential to measure more than a single equivalent size. This study examines a novel method for determining a two-dimensional distribution of two distinct particle properties within the size range from 50nm to 1000nm: the Centrifugal Differential Mobility Analyzer (CDMA). The CDMA enables the simultaneous measurement of both mobility and Stokes equivalent diameters, providing a detailed two-dimensional particle property distribution. This, in turn, allows for the extraction of shape-related information, which is essential for characterizing particles in terms of their chemical composition, reactivity, and other physicochemical properties. This paper presents a detailed evaluation of a first CDMA prototype. First, CFD simulations of the flow field within the classifier are presented in order to assess and understand non-idealities arising from the exact geometry. Subsequently, the transfer function is evaluated by particle trajectory calculations based on the simulated flow field. It can be demonstrated that the simulated transfer functions agree quite well with transfer functions derived from streamlines of an ideal flow field, indicating that the non-idealities in the classifying region are almost negligible in their effect on the classification result. An experimental determination of the transfer function shows additional effects not covered by the previous simulations, like broadening by diffusion and losses due to diffusion and precipitation within the in- and outlet of the classifier. Finally, the determined transfer functions are used to determine the full two-dimensional distribution with regard to the mobility and Stokes equivalent diameter of real aerosols, like spherical particles and aggregates at different sintering stages, respectively.
Keywords: centrifugal differential mobility analysis; 2D-measurement; particle characterization; moving reference frame CFD-simulation; transfer function

The Centrifugal Differential Mobility Analyser – concept and initial validation of a new device for measuring 2D property distributions - Rüther, Torben N.; Rasche, David B.; Schmid, Hans-Joachim (Aerosol Research)
Abstract. Usually for the characterization of nanoparticles, an equivalent property is measured, e.g. the mobility-equivalent diameter. In the case of non-spherical, complex-shaped nanoparticles, one equivalent particle size is not sufficient for a complete characterization. Most of the methods utilized to gain deeper insight into the morphology of nanoparticles are very time-consuming and costly or have bad statistics (such as tandem setups or TEM (transmission electron microscopy)/SEM (scanning electron microscopy) images). To overcome these disadvantages, a prototype of a new compact device, the Centrifugal Differential Mobility Analyser (CDMA), was built, which can measure the full 2D distribution of mobility-equivalent and Stokes equivalent diameters by classification in a cylinder gap through electrical and centrifugal forces. An evaluation method to determine the transfer probabilities is developed and used in this work to compare the measurement results with the theory for the pure rotational behaviour (like the Aerodynamic Aerosol Classifier) and the pure electrical behaviour (like the Dynamic Mobility Analyser). In addition, the ideal 2D transfer function was derived using a particle trajectory approach. This 2D transfer function is a prerequisite for obtaining the full 2D particle size distribution from measurements by inversion.

The POCS-Algorithm—An effective tool for calculating 2D particle property distributions via data inversion of exemplary CDMA measurement data - Rüther, Torben N.; Rasche, David B.; Schmid, Hans-Joachim (Journal of Aerosol Science)
Keywords: POCS; Projection onto convex sets; Data inversion; 2D distribution; CDMA; Centrifugal Differential Mobility Analyzer

Prediction of the transfer function for a centrifugal differential mobility analyzer by streamline functions - Rüther, Torben N.; Schmid, Hans-Joachim (Aerosol Science and Technology)

Sports Preparticipation Evaluation for Healthy Adults: A Consensus-Based German Guideline - Joisten, Christine; Hirschmüller, Anja; Bauer, Pascal; Baum, Erika; Behrens, Meinolf; Berrisch-Rahmel, Susanne; Berrsche, Gregor; Carlsohn, Anja; Cassel, Michael; DeZeuuw, Justus; Dörr, Gesine; Dreher, Michael; et al. (Sports Medicine)
Abstract The benefits of physical activity are undisputed. However, adverse events can occur in rare cases, particularly during high-intensity or prolonged exercise. During physical activity, at-risk patients can experience major cardiac events, whereas adverse events affecting the musculoskeletal system are more common but less severe. A sports preparticipation evaluation (PPE) for apparently healthy adults is designed to detect at-risk individuals and prevent potentially fatal events. This guideline for conducting PPEs was developed by consensus among 16 medical societies and sports associations and is based on previously published guidelines and consensus papers. Sports medicine physicians and potential participants were also surveyed to assess the recommendations’ content, feasibility, and implementation. On the basis of the 20 recommendations developed and agreed upon by the abovementioned entities, PPE comprises individuals’ personal, family, and sports histories, as well as a physical examination. The need for additional examinations (e.g., laboratory parameters, echocardiograms, or stress tests) is determined on the basis of the PPE findings. This approach’s feasibility in various regions, including resource-limited settings, and the extent to which it prevents adverse or potentially fatal events, should be examined in future research.

Selective H2 Gas Sensing Using ZIF-71/In-SnO2 Bilayer Sensors: A Size-Selective Molecular Sieving Approach - Baier, Dominik; Kieke, Laureen; Voth, Sven; Kloß, Marvin; Huck, Marten; Steinrück, Hans-Georg; Tiemann, Michael (ACS Sensors)

Clinical symptom clusters, neurocognitive function, balance and vestibulo-ocular function in athletes with sport-related concussion - Weike, Lea; Reeschke, Rebecca; Reinsberger, Claus (BMJ Open Sport & Exercise Medicine)
Objective This cross-sectional study aimed to investigate subjective and objective deficits of neurocognitive function, balance and vestibulo-ocular performance in athletes with sport-related concussion (SRC) compared with healthy control athletes. Methods 72 patients with SRC and 72 matched healthy controls were included. All participants performed computerised testing of neurocognitive function, device-assisted balance testing and objective evaluation of vestibulo-ocular function (video head impulse and dynamic visual acuity test). Clinical symptom clusters (headache/migraine, anxiety/mood, fatigue, cognitive, vestibular, ocular) were determined for each patient using the Sport Concussion Assessment Tool, 5th edition symptom evaluation. Independent t-tests or Mann-Whitney U tests were calculated to test for group differences in the whole cohort and according to clinical symptom clusters. Results When investigating the whole cohort, significant differences between patients with SRC and control subjects were found in one parameter of balance testing (sway velocity double-firm), with lower performance in the SRC group (p<0.001, r=0.345). The number of symptom clusters assigned to the SRC patients ranged from 0 (no definite cluster) to 6 (all clusters), and all clusters were frequent in the investigated cohort. Patients with vestibular, cognitive and fatigue symptom clusters demonstrated significantly lower performance in balance testing compared with SRC patients without those clusters (p<0.001 to p=0.005, r=0.368–0.439). Additionally, SRC patients presenting with symptoms of the fatigue cluster demonstrated significantly worse performance in vestibulo-ocular testing compared with SRC patients without the fatigue cluster (p=0.006, d=0.781). Conclusion SRC patients presented with variable numbers and qualities of clinical symptom clusters. Some subjective clusters were associated with abnormal objective tests of other clusters (vestibular, cognitive and fatigue with abnormal balance; and fatigue with abnormal vestibulo-ocular performance). Clinical symptom clusters and their overlap should be considered when examining patients with SRC.

Safety and feasibility of exhaustive exercise testing for people with epilepsy - van den Bongard, Franziska; Petersen, Catharina; Reinsberger, Claus (Epilepsy & Behavior Reports)

Hot off the Press: Finding ϵ-Locally Optimal Solutions for Multi-Objective Multimodal Optimization - Rodriguez-Fernandez, Angel E.; Schäpermeier, Lennart; Castellanos, Carlos Hernandez; Kerschke, Pascal; Trautmann, Heike; Schütze, Oliver (Proceedings of the Genetic and Evolutionary Computation Conference, GECCO 2025, NH Malaga Hotel, Malaga, Spain, July 14-18, 2025)

Effects of Different Header Types on Neurocognitive and Vestibular Performance in Youth Soccer Players - Reeschke, Rebecca; Dautzenberg, Lena; Mund, Franziska Katharina; Koch, Thorsten; Reinsberger, Claus (Medicine & Science in Sports & Exercise)
ABSTRACT Purpose Repetitive head impacts due to heading in soccer may bear the potential to induce brain changes. To investigate how brain development is affected by heading, effects of heading exposure on neurocognitive and vestibular performance in adolescent soccer players were prospectively examined. Methods In this longitudinal cohort study, male and female high-level youth soccer players of different ages were enrolled in two seasons. Age-matched athletes of other ball sports were included as controls. Before and after each season, neurocognitive performance (6 domain scores), vestibulo-ocular reflex, dynamic visual acuity, and postural control (sway velocity) were objectively assessed in all athletes. Every soccer training and match during the observation period was videotaped to analyze individual heading exposure. Associations between heading frequency (total, in duels, >20 m flight distance) and pre- to post-changes were investigated via Spearman correlation. Results 103 soccer and 51 control athletes (9-19 years) participated. Neurocognitive scores and sway velocity significantly improved in each season in soccer and control athletes. There were no associations between total heading numbers and changes in any parameter. Over the first season, the more headers played in duels (r = -0.255, 95%CI = -0.474 to -0.006, p = 0.04) and from >20 m distance (r = -0.299, 95%CI = -0.510 to -0.055, p = 0.02) the less psychomotor speed improvement occurred. In the second season, improvements in reaction time were significantly smaller with higher numbers of headers played in duels (r = 0.375, 95%CI = 0.043 to 0.632, p = 0.02) and from >20 m distance (r = 0.359, 95%CI = 0.025 to 0.621, p = 0.03). Conclusions Potential high-impact headers may have affected neurocognitive improvements, exhibiting small to moderate effects. Therefore, more high-impact headers may be more important to consider than solely the overall heading exposure in discussions about adverse effects in youth soccer.

Tagungsbericht: "Kulturkonservatismus, Geistesaristokratie, Ressentiment. Kritische Perspektiven auf literarische Intellektuellendiskurse seit 1918 und ihre gegenwärtige Aktualität (Interdisziplinäre und internationale Tagung in Paderborn, 4.‒7.6.2024)" - Spener, Anna Maria

On token signed graphs - Dalfó, C.; Fiol, M. A.; Steffen, Eckhard (Journal of Algebraic Combinatorics)
We introduce the concept of a k-token signed graph and study some of its combinatorial and algebraic properties. We prove that two switching isomorphic signed graphs have switching isomorphic token graphs. Moreover, we show that the Laplacian spectrum of a balanced signed graph is contained in the Laplacian spectra of its k-token signed graph. Besides, we introduce and study the unbalance level of a signed graph, which is a new parameter that measures how far a signed graph is from being balanced. Moreover, we study the relation between the frustration index and the unbalance level of signed graphs and their token signed graphs.

Synthesizing Speech with Selected Perceptual Voice Qualities – A Case Study with Creaky Voice - Rautenberg, Frederik; Seebauer, Fritz; Wiechmann, Jana; Kuhlmann, Michael; Wagner, Petra; Haeb-Umbach, Reinhold (Interspeech 2025)

Bryant, Jonathan: Compassion and the Characterization of the Markan Jesus (Biblical Interpretation Series, Band: 223) - Breuer, Saskia Rebecca (ThRv)

Du hast es Dir verdient.“ Ökonomische Perspektiven auf den (selbstgestalteten) Tod im Roman Die Königin der Berge (2018) und das digitale „Leben nach dem Tod“ in der Serie Upload (seit 2020) - Harmening, Anda-Lisa (The (Un)Speakability of Death. Contemporary Literarisations and Visualisations of Dying)